2008
DOI: 10.1002/hep.22336
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention and antioxidant therapy in children with nonalcoholic fatty liver disease

Abstract: No proven treatment exists for nonalcoholic fatty liver disease (NAFLD) in children and adolescents. We sought to determine the efficacy of lifestyle intervention with or without antioxidant therapy in pediatric NAFLD. A total of 53 patients (age 5.7-18.8 years, 37 boys) were included. Lifestyle intervention consisting of a diet tailored to the patient's calorie needs, and increased physical activity was prescribed in all. Patients were concomitantly randomized to alpha-tocopherol 600 IU/day plus ascorbic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
305
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(339 citation statements)
references
References 39 publications
6
305
0
9
Order By: Relevance
“…Secondly, there are a lack of regular medical physical examinations conducted amongst chronic virus carriers and many other people are asymptomatic and unaware of their carrier status (Lok et al, 1991). Thirdly, there is a lack of public knowledge about factors such as lifestyle which are important for the prevention of hepatitis and liver cancer (Nobili et al, 2008;Giles et al, 2013). Lastly, liver cancer in adults has a poor prognosis, because it tends to be diagnosed at the advanced stages of the disease, and also, many people with liver cancer also develop comorbid liver disease such as cirrhosis, which is frequently fatal, leading to low survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are a lack of regular medical physical examinations conducted amongst chronic virus carriers and many other people are asymptomatic and unaware of their carrier status (Lok et al, 1991). Thirdly, there is a lack of public knowledge about factors such as lifestyle which are important for the prevention of hepatitis and liver cancer (Nobili et al, 2008;Giles et al, 2013). Lastly, liver cancer in adults has a poor prognosis, because it tends to be diagnosed at the advanced stages of the disease, and also, many people with liver cancer also develop comorbid liver disease such as cirrhosis, which is frequently fatal, leading to low survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Eight RCTs (373 participants, 39% diabetic; six RCTs with a low risk of bias, four RCTs with post-treatment histology) assessed the effect of lifestyle-or drug-induced weight loss in NAFLD [6][7][8][9][10][11][12][13] (ESM Table 1). …”
Section: Weight Lossmentioning
confidence: 99%
“…Dietary modifications including improving the quality of school dinners and increased exercise are critical interventions in reducing patient body weight. A study that used an improvement in liver histology as its primary endpoint demonstrated that two years of increased physical activity and lifestyle intervention with an individual calorie diet resulted in a significant improvement in the severity of steatosis, inflammation and hepatocyte ballooning and the NAFLD activity score [128]. The study also reported an improvement in liver enzymes, insulin resistance and serum lipid levels [128].…”
Section: Key Management Issuesmentioning
confidence: 99%
“…A study that used an improvement in liver histology as its primary endpoint demonstrated that two years of increased physical activity and lifestyle intervention with an individual calorie diet resulted in a significant improvement in the severity of steatosis, inflammation and hepatocyte ballooning and the NAFLD activity score [128]. The study also reported an improvement in liver enzymes, insulin resistance and serum lipid levels [128]. The TONIC study, a double-blind placebo controlled trial compared vitamin E or metformin for 96 weeks [129].…”
Section: Key Management Issuesmentioning
confidence: 99%